2018
DOI: 10.1007/s00345-018-2295-6
|View full text |Cite
|
Sign up to set email alerts
|

Local staging with multiparametric MRI in daily clinical practice: diagnostic accuracy and evaluation of a radiologic learning curve

Abstract: PurposeTo estimate the diagnostic accuracy of multiparametric MRI (mpMRI) for the detection of locally advanced prostate cancer (T-stage 3–4) prior to radical prostatectomy, in a multicenter cohort representing daily clinical practice. In addition, the radiologic learning curve for the detection of locally advanced disease is evaluated.MethodsPreoperative mpMRI findings of 430 patients (2012–2016) were compared to pathology results following radical prostatectomy. The diagnostic accuracy (sensitivity, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
(36 reference statements)
1
7
0
1
Order By: Relevance
“…Furthermore, there is a potential role for mpMRI in not only localizing tumor but also in identifying the areas of more aggressive cancer that could be selectively targeted by biopsy or for focal ablation therapy. Several studies have shown that both DWI and spectroscopic imaging are correlated with the Gleason grade [5,[18][19][20]. As confirmed by our pathologic-radiologic comparison, low ADC values are associated with an increasing Gleason score.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, there is a potential role for mpMRI in not only localizing tumor but also in identifying the areas of more aggressive cancer that could be selectively targeted by biopsy or for focal ablation therapy. Several studies have shown that both DWI and spectroscopic imaging are correlated with the Gleason grade [5,[18][19][20]. As confirmed by our pathologic-radiologic comparison, low ADC values are associated with an increasing Gleason score.…”
Section: Discussionsupporting
confidence: 85%
“…With higher sensitivity and specificity, mpMRI is increasingly used in guiding biopsies in biopsy-negative and previously negative cases. Also, it is used for proper staging, risk stratification and decision-making and is being incorporated in clinical nomograms [5,8,9,[13][14][15][16]. Moreover, MR tractography helps visualizing the prostatic nerve bundles guiding the nerve-sparing surgery to reserve the erectile function [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI techniques included only partly diffusion-weighted (DW) imaging, and no standardized reporting was used. Moreover, Jansen et al [38] observed comparable sensitivity for the prediction of EPE between 133 high-risk and 297 low-risk patients (49% vs 42%, p = 0.5).…”
Section: Multiparametric Mrimentioning
confidence: 93%
“…Risk stratification. Several studies were found to assess the performance of MRI according to different risk groups [8,19,20,24,38,40,46,59,62,66,70,75]. While better performance for high-risk patients has been presumed in literature, the data actually remain inconclusive.…”
Section: Multiparametric Mrimentioning
confidence: 99%